Successful business intelligence system for SME: An analytical study in Malaysia - Qushem, Umar; Zeki, Akram M.; Ibrahim, Adamu Abubakar (IOP Publishing, 2017)
While many larger organizations is adhering to a new level of competence by adoption of advanced Business Intelligence (BI) systems, in the same time there are other small-medium companies who are left behind in terms of updating them for better success in the industry. Thus the aim of the research is to identify Small and Medium Enterprise (SME) specific determinants for Business Intelligence efficiency which will lead those organizations a better understanding of development and testing of BI framework in the business world. In this study, it is therefore considered extensive literature reviews to measure the efficiently factors and proposed a holistic conceptual framework. In the same time, feedbacks of the Business Intelligent experts were taken into consideration to provide new insights for SME companies to ensure where to focus and which type of sector is crucial for an SME organization in order to be successful in parallel with Big organizations. Thus in this regard, Quantitative Survey research method is used and Statistical analysis were used for analyzing the data. The results revealed that SME Companies should focus on Environmental factor (EF) as it is the most identified factor lead BI efficiency in Business Organization